On cloaking behaviors of malicious websites. Issue 101 (February 2021) - Samarasinghe, Nayanamana; Mannan, Mohammad
Abstract: Malicious websites often mimic top brands to host malware and launch social engineering attacks, e.g., to collect user credentials. Some such sites often attempt to hide malicious content from search engine crawlers (e.g., Googlebot), but show harmful content to users/client browsers—a technique known as cloaking . Past studies uncovered various aspects of cloaking, using selected categories of websites (e.g., mimicking specific types of malicious sites). We focus on understanding cloaking behaviors using a broader set of websites. As a way forward, we built a crawler to automatically browse and analyze content from 100000 squatting (mostly) malicious domains—domains that are generated through typo-squatting and combo-squatting of 2883 popular websites. We use a headless Chrome browser and a search-engine crawler with user-agent modifications to identify cloaking behaviors—a challenging task due to dynamic content, served at random; e.g., consecutive requests serve very different malicious or benign content. Most malicious sites (e.g., phishing and malware) go undetected by current blacklists; only a fraction of cloaked sites (127, 3.3%) are flagged as malicious by VirusTotal. In contrast, we identify 80% cloaked sites as malicious, via a semi-automated process implemented by extending the content categorization functionality of Symantec's SiteReview tool. Even after 3 months of observation, nearly a half (1024, 45.4%) of the cloaked sites remained active, and only a few (31, 3%) of them are flagged by VirusTotal. This clearly indicate that existing blacklists are ineffective against cloaked malicious sites. Our techniques can serve as a starting point for more effective and scalable early detection of cloaked malicious sites.